Preoperative levels of folate receptor-positive circulating tumor cells in different subtypes of early-stage lung adenocarcinoma: Predictive value for determining extent of surgical resection - Zhou, Chao; Zhao, Ran; Zhao, Ruiying; Wang, Ansheng; Li, Wentao (Frontiers in Oncology, 2023)
Background: To evaluate the correlation between preoperative folate receptor-positive circulating tumor cells (FR+CTCs) levels and clinical characteristics and histologic subtype of early-stage lung adenocarcinoma, as well as the predictive value of FR+CTCs in the preoperative determination of the extent of surgical resection. Patients and Methods: In this retrospective, single-institution, observational study, preoperative FR+CTC levels in patients with early-stage lung adenocarcinoma were detected by ligand-targeted enzyme-linked polymerization. The receiver operating characteristic (ROC) analysis was used to identify the optimal predictive value of FR+CTC. Results: No significant difference was observed in FR+CTC levels among patients with adenocarcinoma in situ (AIS), minimally invasive adenocarcinoma (MIA), and invasive adenocarcinoma (IAC) (P=0.813). In the non-mucinous adenocarcinoma group, no difference was observed among patients with lepidic-, acinar-, papillary-, micropapillary-, solid-, and complex glands-predominant growth patterns (P=0.053). Significant differences were observed between the presence and absence of the micropapillary subtype [(11.21 (8.22-13.61) vs. 9.85 (7.43-12.63), P=0.017], the presence and absence of the solid subtype [12.16 (8.27-14.90) vs. 9.87 (7.50-12.49), P=0.022], and the presence and absence of the advanced subtypes including micropapillary, solid, or complex glands [10.48 (7.83-13.67) vs. 9.76 (7.42-12.42), P=0.032]. The FR+CTCs level was correlated with the differentiation degree of lung adenocarcinoma (P=0.033), visceral pleural invasion (VPI) of lung carcinoma (P=0.003), and lymph node metastasis of lung carcinoma (P=0.035). Conclusion: FR+CTC can potentially be the predicted value of the presence of aggressive histologic patterns (micropapillary, solid and advanced subtypes), differentiation degree, VPI, and lymph node metastasis of IAC. FR+CTC combined with intraoperative frozen sections can be a more effective method to guide resection strategy for cT1N0M0 IAC with high-risk factors.